Relokasi Pedagang Pasca Revitalisasi Pasar Johar Semarang - Wibowo, Naufal Farras Abhista; Rahdriawan, Mardwi (Jurusan Perencanaan Wilayah dan Kota, 2024)
The purpose of this study was to analyze the readiness of traders from the South Johar Sub-Rayon from the relocation site back to the Johar Market, Semarang. The study used quantitative methods with variables, namely identification of relocation policies, assessing the readiness and perceptions of traders and processed by descriptive techniques and scoring analysis. Data collection techniques are questionnaires, interviews, field observations, document reviews and literature studies. The results of the research are traders are very ready to return to Pasar Johar Semarang and overall conditions are better such as the conditions of zoning arrangements, circulation, waste management systems, drainage systems and waste water management, availability of green open spaces and safety systems in buildings. There are two aspects that are deemed inadequate, namely the condition of kiosks and stalls as well as the existence of parking and loading and unloading places, but traders are required to adapt because Johar Market is a cultural heritage building so it must be rearranged and is expected to be able to adjust trading strategies by making Johar Market Semarang as a showcase of commodities that are sold, and for warehouses can wait for the construction of the Main Market in Rejomulyo.